1975
DOI: 10.1002/jss.400030209
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent fluorescence depolarization and lifetime studies of myosin subfragment‐one in the presence of nucleotide and actin

Abstract: Time-dependent fluorescence depolarization and lifetime studies have been made on myosin subfragment 1 to obtain information about mobility changes and dye environment changes when different nucleotides are added. Data are reported for static and actively hydrolyzing systems containing G- and F-actin. Preliminary data indicate that myosin labeled with the fluorophore 1, 5 IAEDANS and treated with DTT preserves its actin-activated Vmax. S1 prepared in this manner gives lifetime changes which are nearly identica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
29
1

Year Published

1976
1976
1990
1990

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 17 publications
7
29
1
Order By: Relevance
“…Inhibition of K + (EDTA)-ATPase and activation of Ca 2+ -ATPase indicated specific labeling of the SHi thiols. The Ca 2+ -ATPase of fully labeled cardiac myosin (2 dyes/myosin) was activated between 6-and 7-fold, in agreement with previous findings for skeletal myosin (Mendelson et al, 1975) which indicated (as in the case of the spin label) that a fairly specific labeling of SH, had occurred.…”
Section: Fluorescence-labeled Cardiac Myosinsupporting
confidence: 90%
See 1 more Smart Citation
“…Inhibition of K + (EDTA)-ATPase and activation of Ca 2+ -ATPase indicated specific labeling of the SHi thiols. The Ca 2+ -ATPase of fully labeled cardiac myosin (2 dyes/myosin) was activated between 6-and 7-fold, in agreement with previous findings for skeletal myosin (Mendelson et al, 1975) which indicated (as in the case of the spin label) that a fairly specific labeling of SH, had occurred.…”
Section: Fluorescence-labeled Cardiac Myosinsupporting
confidence: 90%
“…The effect of actin addition on saturation of the spin-labeled myosin EPR spectrum (Seidel, 1973) was calculated from R3 (actomyosin)/R-j (myosin) where R3 is the ratio of the amplitude of peak 3 (the midpeak) at 180 mW (high microwave power) to the amplitude of the same peak recorded at 3.2 raW (low power). Fluorescence depolarization measurements were made at 5°C using the nanosecond-decay fluorimeter previously described (Mendelson et al, 1975).…”
Section: Methodsmentioning
confidence: 99%
“…This suggested these SH groups could move from 14 A to as close as 7 A upon binding of MgADP. We have recently provided further support for the proximal distance between SH-1 and SH-2 of [3][4][5] A based on evidence of simultaneous chelation of these two SH groups by a single-exchange-inert Co(III) phenanthroline complex (13,14).…”
mentioning
confidence: 81%
“…The fluorometer used in this work is substantially that previously used to study the segmental flexibility of myosin (5), and recently modified to study the species in an actin-(S-1) ATPase system (6). In each experiment 2.5 X 107 photons were collected in 25 min.…”
mentioning
confidence: 99%